Identification and Molecular Characterization of Telosma Mosaic Virus (TelMV) and East Asian Passiflora Virus (EAPV) from Patchouli in China - Asma Aziz; Na Li; Xiaoqing Wang; Linxi Wang; Yougen Wu; Muhammad Zeeshan Ul Haq; Zhaoji Dai; Hongguang Cui (Viruses)
Patchouli is a valuable medicinal herb and cash crop in China, but viral infections cause significant yield losses. This study identified six viruses in patchouli transcriptome data, including the first-ever detection of East Asian Passiflora Virus (EAPV) in patchouli. RT-PCR validated three viruses from diseased patchouli plants in Haikou, China: telosma tosaic virus (TelMV), broad bean wilt virus-2 (BBWV-2), and pogostemom alphacytorhabdovirus 1 (PogACRV1_Pog). The complete genomic sequence of TelMV from patchouli (TelMV) was determined, revealing a 9691-nucleotide RNA genome encoding a 3083-amino-acid polyprotein. Comparative analysis showed 77.66% to 81.01% nucleotide sequence identity with previously reported TelMV isolates. TelMV was also shown to be infectious in Nicotiana benthamiana through sap rub-inoculation. Additionally, a large portion of the EAPV genome was reconstructed from RNA-seq data, with coat protein analysis confirming its identity. This study presents the first complete TelMV genome in patchouli and the first detection of EAPV in the plant.